KESETARAAN GENDER DI PESANTREN DALAM KAJIAN LITERATUR - Najib Jauhari; Siti Malikah Thowaf (Sejarah dan Budaya : Jurnal Sejarah, Budaya, dan Pengajarannya, 2019)
The study of Islamic science in the world of pesantren has greatly contributed to shaping the religious understanding of the people, including in the issue of jender equality. The material studied at pesantren refers to the yellow books, most of them are fiqh and normative norms that tend to be patriarchal and form jender-biased understanding. This study describes: (1) Jender background thinking (2) Jender theoretical studies (3) Jender studies in Islam (4) How jender studies in pesantren. As a result of the literature review, the researcher acts as the main instrument; conducting a study of documents, books related to the topic. Descriptive, inductive-comparative data analysis was performed. For the validity of information, review the adequacy of references and peer reviews. This study will be useful for the field of jender studies and pesantren education. Islamic education develops along with the demands of the times, pesantren do not hesitate to make changes for the benefit. Many pesantren are always looking for, and are quite open to innovations that benefit the people.Kajian ilmu keislaman di dunia pesantren besar andilnya dalam mengonstruksi konsep keagamaan umat, termasuk dalam isu kesetaraan jender. Kitab-kitab kuning yang dikaji di pesantren, kebanyakan berupa kaidah fiqh, bersifat normative, cenderung patriarkis dan membentuk pemahaman yang bias jender. Kajian ini mendeskripsikan: (1) Latar belakang pemikiran jender (2) Kajian teoritik jender (3) Kajian jender dalam Islam (4) Bagaimana kajian jender di pesantren. Sebagai hasil kajian literatur, peneliti berperan sebagai instrumen utama; melakukan kajian dokumen, buku-buku yang terkait dengan topik. Dilakukan analisis data secara deskriptif, induktif-komparatif. Untuk keabsahan informasi ditelaah  kecukupan referensi serta review teman sejawat. Kajian ini akan bermanfaat bagi bidang kajian jender dan pendidikan kepesantrenan. Pendidikan Islam berkembang bersamaan dengan tuntutan jaman, pesantren tidak segan untuk mengadakan perubahan-perubahan demi kemaslahatan. Banyak pesantren yang selalu mencari, dan cukup terbuka terhadap inovasi-inovasi yang bermanfaat bagi umat..